Breeding increases grain yield, zinc, and iron, supporting enhanced wheat biofortification - Velu, Govindan; Atanda, Sikiru Adeniyi; Singh, Ravi P.; Huerta Espino, Julio; Crespo-Herrera, Leonardo A.; Juliana, Philomin; Mondal, Suchismita; Joshi, Arun Kumar; Bentley, Alison R. (Wiley, 2022)
Estimation of the rate of genetic gain over time allows quantification of breeding progress. Here we report on the rate of grain yield and zinc (Zn) concentration increase over 11 yr of targeted wheat (Triticum aestivum L.) biofortification breeding at the International Maize and Wheat Improvement Center (CIMMYT). Data from yield trials evaluated across multiple locations in South Asia and beyond showed that average annual increases in grain yield potential of ∼1.5% and 0.9% per year gains for grain Zn and Fe concentrations. Across locations in all countries, mean yields of the five highest-yielding entries showed an annual gain of 109 kg ha−1 yr−1 in yield and 0.3 mg kg−1 for grain Fe and Zn as well as 0.66 g for the yield component thousand-grain weight. There was a strong positive correlation between Fe and Zn (r =.42) across locations, whereas no genetic no correlation was observed between grain yield and Zn (r =.05) across locations. Despite the slight negative relationship between yield and Zn, through targeted crossing and development of large segregating populations we were able to identify transgressive segregants combining increased yield and Zn concentrations. Significant differences between lines for grain micronutrient concentrations were detected, and significant location effects on grain Zn and Fe concentrations were observed. These results demonstrate that continuous and simultaneous genetic gain for grain yield and concentrations of Fe and Zn is possible in elite spring bread wheat lines with potential to deliver global impact through identification of superior parents for use by national breeding programs and the release of biofortified wheat cultivars.